Alveolar ridge augmentation in mandible by use the modified distractor. - Feras Sulaiman; Issam Alkhouri; Maher Al-assaf (University Library System, University of Pittsburgh, 2022)
Objective: The aim of the present study was to evaluate the horizontal and the vertical alveolar distraction osteogenesis using modified alveolar distractor. Study design: The sample consisted of 7 patients presenting horizontally and vertically deficient edentulous ridges were treated by distraction osteogenesis with a modified Alveolar distractor. The surgical procedure was carried out with the patient under local anesthesia. After the osteotomy was performed with pizosurgery, the distractor was placed on the segmental bone over the gingiva for 3 months. The rate of distraction was 0.5 mm/twice a day. Results: The mean of horizontal alveolar before using the distractor was 4.70 mm (SD 0.31 mm) The mean of horizontal alveolar after using the distractor was 8.30 mm (Sd 0.59 mm). The mean of actual gain in bone horizontal at the end of the distraction period was 3.58 mm (SD 0.15 mm). The mean of height alveolar before using the distractor was 6.67 mm (SD 0.46 mm) The mean of height alveolar after using the distractor was 12.59 mm (SD 0.52 mm). The mean of actual gain in bone height at the end of the distraction period was 5.92 mm (SD 0.25 mm). Conclusion: It was concluded that the modified alveolar distractor seems to be an effective to treat horizontal and vertical alveolar ridge deficiencies, and distraction osteogenesis can be considered a safe and effective procedure for gaining bone in the horizontal and the vertical dimension of the alveolar.